PROJECT BASED LEARNING MODEL (PjBL) TO IMPROVE COLLABORATION SKILLS AND STUDENT COGNITIVE LEARNING RESULTS - Aifah, Dewi Nur; Astriani, Dyah (PENSA E-JURNAL: PENDIDIKAN SAINS, 2024)
This research aims to describe the improvement in collaboration skills and cognitive learning outcomes of students using the PjBL learning model on mixed separation material. This type of research is quantitative research with a one-group pretest-posttest design. Data collection techniques use observation of collaboration skills, cognitive learning outcomes tests, and distribution of questionnaires. The results obtained from this research show that students' collaboration skills have increased at each meeting, from the collaborative category to very collaborative. Student learning outcomes have increased as evidenced by the average N-Gain score in the medium category. The results of the paired t-test show that there is a significant difference between cognitive learning outcomes before and after the implementation of the PjBL learning model. Based on the results obtained, it can be concluded that the implementation of the PjBL learning model has succeeded in improving collaboration skills and cognitive learning outcomes for junior high school students.